2022
DOI: 10.1002/pc.26488
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of polyurethane‐coated carbon fiber and electron beam irradiation on the thermal/mechanical properties and long‐term durability of polyamide‐based thermoplastic composites

Abstract: To attain thermoplastic polymer composites with enhanced thermal and mechanical properties as well as long‐term durability, in this study, polyurethane‐coated carbon fiber (CF) and electron beam (EB) irradiation are adopted as an effective reinforcing filler and efficient crosslinking process, respectively. For this purpose, polyamide 6 (PA)‐based composites with different CF contents of 1–10 wt% were fabricated through melt‐compounding and compression molding, and then irradiated with various EB doses of 50–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Kim et al [ 121 ] used PU polymer sizing and EB irradiation to increase the CF and PA6 matrix interfacial bonding. CF coated with PU sizing agent was melt compounded with PA6 pellets and compression molded to form CF/PA6 composites.…”
Section: Fibre Surface Treatment Methodsmentioning
confidence: 99%
“…Kim et al [ 121 ] used PU polymer sizing and EB irradiation to increase the CF and PA6 matrix interfacial bonding. CF coated with PU sizing agent was melt compounded with PA6 pellets and compression molded to form CF/PA6 composites.…”
Section: Fibre Surface Treatment Methodsmentioning
confidence: 99%
“…On the other hand, the stepped isothermal method (SIM) compensates for the shortcoming of the traditional TTS test and needs only one specimen to be tested at various step-up temperature levels. [45][46][47][48] To examine the long-term durability of mechanical properties, the elastic storage moduli can be measured as functions of temperature and frequency by adopting the SIM with the assumption that the strain is a thermal activation process. Thus, based on the TTS principle, storage modulus values measured as a function of frequency over a short period at various temperatures need to be horizontally shifted so that they fit well with the long-term mechanical durability curve measured along the axis of frequency through the shift factor (a T ), which leads to the creation of a frequency-dependent master curve at a reference temperature.…”
Section: Dynamic Mechanical and Long-term Mechanical Durabilitymentioning
confidence: 99%
“…Conductive composites based on organosilicon elastomers (silicones) [ 22 ] may have a functional feature associated with self-regulation of the heating temperature [ 23 ]. Studies related to the effect of MWCNTs on heat release in a flexible nanomodified elastomer are presented in the work and it was found that the heat release power can be represented in the form of regression equations, where there is a dependence of heat release on temperature, applied tensile strain and electrical heating [ 24 ].…”
Section: Introductionmentioning
confidence: 99%